The Quality of Life of Mothers Who Have Children with Autism Spectrum Disorder - Pertiwi, Sylvidire Maharani Hayu; Irwanto, Irwanto (Indonesian Journal of Disability Studies, 2020)
Autism Spectrum Disorder (ASD) is a complex intellectual and developmental disability clinically diagnosed when s/he is 2 or three years old. These children demand special care to meet their special needs to enable optimized potentials in their development. This qualitative study aims at understanding the stressors affecting the quality of life of the primary care-giver. Parenting for children with ASD is usually more complicated and demanding than for children without disabilities. Four case studies were selected to represent typical mothers of ASD children in different phases of development. Their ages ranged from 29-50 years old and the ages of their children were 6 to 22 years old. Research credibility is constructed through interviews with significant others and observation of social media activities. The instrument for the study is WHO-QoL-BREF which is adjusted for an interview protocol. The results indicated that mothers who were not supported by their spouse and family members often had to deal with the uncertain future alone. Those who felt accomplished in caring for their children were strengthened by the parenting experiences. Support from professionals is crucial for mothers in addition to support from significant others and peers, in maintaining their quality of life.